The nature of disease pathology for the health professions - McConnell, Thomas H. (Lippincott Williams & Wilkins, 2007)
This textbook is based on the premise that students learn better when material is easy to read, lively, and engaging. The author's readable style easliy guides you through the causes and consequences of common diseases and is punctuated by humor, case studies, and absorbing tales. You'll gain an understanding of pathology and the skills needed to use what you've learned in clinical settings. The book's 24 chapters are divided among 3 sections: 1--Mechanisms of Health and Disease; 2-- Disorders of Organ Systems; and 3--Disorders of the Stages and States of Life